Cost Minimization Analysis Pasien JKN Rawat Jalan Penyakit Hipertensi di RS “X” Kota Surabaya - Kusuma Wardani, Deva Rahayu Nurindah; Amarullah, Adinugraha; Rahmawati, Dewi (Journal of Health Management Research, 2023)
Background: Hypertension is a medical condition where there is an increase in blood pressure which can increase morbidity and mortality. Hypertension requires treatment for a long time and is relatively expensive. Aims: This study aims to describe the cost of antihypertensive therapy and to analyze the most cost-minimizing treatment for JKN outpatients with hypertension at "X" Hospital, Surabaya City. Methods: This research is a non-experimental research with quantitative methods and data collection is done retrospectively. The data analyzed is treatment therapy data for the period January - December 2022. The sample used was 96 patients. The cost measured is the direct medical cost of outpatients. The data was analyzed using the method of cost minimization analysis.. Results: The results showed that 58% of patients were female and 42% male with 1% of patients aged 21-40 years, 41-60 years of 25%, and ≥ 61 years of 74%. CMA results for Imidapril of Rp. 200.870,00, Bioprexum Rp. 348.683,33.00, Candesartan Cilexetil Rp. 103.840,23, Amlodipine Besilate Rp. 96.108,375, Nifedipine Rp. 254.538,00, Bisoprolol Rp. 155.045,00, and Carvedilol Rp. 148.955,00. Conclusion: Amlodipine Besilate is the most cost minimized antihypertensive therapy compared to other antihypertensive therapies with an average direct cost of Rp. 96,108.375/patient.